Creatividad y su aporte en la producción de cuentos en el área de lengua y literatura en los estudiantes de la Unidad Educativa Francisco Robles del cantón Babahoyo, provincia los Ríos. - Guerra Proaño, Nancy Elvira (2018)
The problem of study in students is focused on the lack of methods to develop creativity, the classes must carry out a certain form of pedagogy in which a stimulus is applied to the automatic resolution of problems in the student, enough to be able to create an original story by itself. According to basic education studies, in several countries such as Uruguay, Ecuador, among others, their educational system is revised and adapted to the methods most used. The media obstruct the critical, active and innovative capacity of the student. For this research you can look for ways to develop creativity with dynamics, games and activities focused on the resolution of problems by themselves, the cognitive ability of each student, these processes are implemented at an early age in order to have a good result in the students of the educational unit francisco oaks of Babahoyo canton, the rivers province. Studies show that the majority of students in the francisco oaks educational unit have a good creativity in putting them into activities related to creating something original, because their creative training is very well complemented to the point of creating short stories with very good plot and plot, but there are very few who come to stand out.